Treatment of produced water using graphene - Abou Chacra, Lamis (2016)
A Master of Science thesis in Chemical Engineering by Lamis Abou Chacra entitled, "Treatment of produced water using graphene," submitted in January 2016. Thesis advisor is Dr. Taleb Ibrahim. Soft and hard copy available.